Da saga do pantaneiro eu faço esse meu cantar : circularidade e hibridismo cultural do rasqueado da fronteira Oeste a partir da obra de Guapo - Maluf, Henrique Rodrigues Jabur (2024)
The present dissertation aims to investigate the historical circuit surrounding the "rasqueado pantaneiro" of the western border of Mato Grosso, based on the life and artistic trajectory of Milton Pereira de Pinho, also known as Guapo. The objective is to explore the artistic and cultural universe of Cáceres-MT, considering the circularity and cultural hybridity inherent in the "rasqueado pantaneiro" musical genre, with a focus on the song "Canto Guacho" from 1984. Guapo's work holds cultural and historical significance, encompassing five albums, four books, productions, international shows, among others, distributed over more than 50 years dedicated to the art and the Pantanal cultural universe. For this purpose, we used the artist's digital archive available at https://miltonguapo.com.br/. In addition to Guapo, we also briefly surveyed other composers from the city of Cáceres, such as Adão da Harpa, Emerson Dorado, and Rocco Martins, contextualizing the musical genre in the western border. To do this, we conducted semi-structured interviews and analyzed one song from each aforementioned composer and two from Guapo, addressing poetic and musical parameters in order to investigate how they converge and diverge within their cultural contexts, using an interdisciplinary approach between History and Music. Beyond the issues of these sciences, the circumstances that led to the emergence of "rasqueado" in Brazil, in Mato Grosso, and consequently in Cáceres, must be considered in terms of the transculturation between Brazil, Paraguay, and Bolivia, as well as the experiences of these individuals in the Pantanal. These cross-border processes and the identity construction of these artists reflected in a "cacerense" way of composing the "Rasqueado".